Impact of cockroach allergens on the immune response as an asthma trigger - Bena, Maryangela Godinho Pereira; Araújo, Iêda Maria Silva; Paz, Bruna Katarine Beserra; Pinheiro, Giselmo Lopes; Falcai, Angela (Ciência e Natura, 2018)
This work is a literature review that aims to provide a comprehensive overview of asthma and show the importance of cockroach allergens as a trigger for the disease, as well as highlight the immune mechanisms involved. Asthma is a public health problem, with a high global prevalence, especially in children and adolescents, characterized by type 1 hypersensitivity. It is a multifactorial disease triggered by environmental, genetic, and immunological factors. Several articles have correlated asthma with cockroach allergens, and their prevalence has been increasing. Environmental conditions, low income, urban centers, and lack of basic sanitation are associated with cockroach infestations that contribute to asthma attacks. Identifying cockroach proteins capable of triggering asthma, and elucidating the immunological mechanisms involved in responding to cockroach allergens is essential. This review concludes that the prevalence of asthma triggered by cockroach allergens is high. Only two allergenic cockroaches, Blatella germanica and Periplaneta americana, have been identified with 11 and 12 allergens, respectively. Furthermore, there are very few studies that detail how the immune system of asthmatic children behaves in the face of these cockroach allergens.